1975
DOI: 10.1071/ea9750773
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating poultry feedstuffs in terms of their metabolizable energy content and chemical composition

Abstract: The metabolizable energy values (ME) of 16 feed ingredients available in Australia were determined with broiler chicks of both sexes. The chickens were fed test diets in which the feed ingredients replaced dextrose in a basal diet.The mean coefficient of variation was low in each determination of ME (range 0.78 to 1.20, mean 0.94 per cent). Sex had no significant effect on the ME value of most feedstuffs with the exception of oats, where ME values were significantly higher for female than for male chicks (P < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Farrell (19'15) reported between breed differences in heat production and AME utilization for tissue synthesis; differences in daily maintenance energy requirements (AMETokg body wt) among broiler lines were reported by Pym and Farrell (1917). Differences in optimal calorie:protein ratios between strains of White Leghorn hens were identified by Liljedahl et al (1913) (Guirguis 1975). Interactions between sex, fat and fish meal were reported to affect AME values but the reason is obscure (Guirguis l976a,b).…”
Section: Control Of Feed Intakementioning
confidence: 97%
See 1 more Smart Citation
“…Farrell (19'15) reported between breed differences in heat production and AME utilization for tissue synthesis; differences in daily maintenance energy requirements (AMETokg body wt) among broiler lines were reported by Pym and Farrell (1917). Differences in optimal calorie:protein ratios between strains of White Leghorn hens were identified by Liljedahl et al (1913) (Guirguis 1975). Interactions between sex, fat and fish meal were reported to affect AME values but the reason is obscure (Guirguis l976a,b).…”
Section: Control Of Feed Intakementioning
confidence: 97%
“…Titus (1958) extended and refined the work of Fraps et al (1940) by deriving a series of 'percentage multipliers' which permit calculation of the AME values of individual f'eedingstuffs. Opstvedt (1973) (Opstvedt 1976 (Janssen and Terpstra 1972;Jannsen et al 1975Jannsen et al , 1976Janssen 1916Janssen , 1919 (Connor et al 1976) and oats (Davidson et al 1978 Carpenter and Clegg (1956), Bolton (1962b) and Sibbald et al (1963) whereas the equations ofTitus (1958) produced reasonably accurate data (Guirguis 1975 Coates et al 1911a). No equation was able to give satisfactory TME values for wheats but the TME values of oats (Sibbald and Prtce l9lla) and barley (Sibbald and Price 1916b) were well predicted by some equations.…”
Section: Control Of Feed Intakementioning
confidence: 99%
“…Young et al (1977), experimenting with pigs, reported a ME value of 2.17 kcal/g dry matter for meat and bone meal. Potter and Matterson (1960) in chicks trials reported ME value of 1.98 kcal/g dry matter, while Guirguis (1975) observed that ME of meat and bone meal averaged 2.55 kcal/g matter.…”
Section: Experiments 7610mentioning
confidence: 99%
“…meal from different sources in experiments with chicks and observed ME values ranging from 2.0 to 3.05 kcal/g dry matter. However, Guirguis (1975) reported a value of 3.52 kcal/g dry matter as the ME of peanut meal fed to chicks. Young et (1977), discussing the discrepancy in the range of values reported for DE of soybean meal, attributed the range in reported values to Also, the peanut meal used in this study was mechanically extracted, and as Lodhi et (1976) observed, ME content of peanut cake derived from single-phase extraction was higher than that of four phase extraction.…”
Section: Experiments 7711mentioning
confidence: 99%
See 1 more Smart Citation